Gut Microbiota Comparison Between Intestinal Contents and Mucosa in Mice With Repeated Stress-Related Diarrhea Provides Novel Insight - Zhang, Chen-Yang; Peng, Xin-Xin; Shao, Hao-Qing; Li, Xiao-Ya; Wu, Yi; Tan, Zhou-Jin (Frontiers in Microbiology, 2021)
Repeated stress-related diarrhoea is a kind of functional bowel disorders (FBDs) which are mainly stemming from dysregulation of the microbiota-gut-brain axis mediated by a complex interplay of 5-hydroxytryptophan (5-HT). Intestinal contents and intestinal mucosa microbiota belong to two different community systems, and there remains largely unknown in the role of the two microbiota community systems in repeated stress-related diarrhoea. In order to ascertain the difference of composition and the potential function between intestinal contents and intestinal mucosa microbiota response on repeated stress-related diarrhoea, we collected intestinal contents and mucosa of the mice with repeated stress-related diarrhoea for 16S rRNA Pacbio SMRT gene full-length sequencing; and with the digital modeling method of bacterial species abundance, the correlations among the two microbiota community systems and serum 5-HT concentration were analyzed. We found that the microbiotal composition differences both in intestinal contents and mucosa were consistent throughout all the phylogenetic ranks, with an increasing level of resolution. Compared with intestinal contents microbiota, the diversity and composition of microbiota colonized in intestinal mucosa are more sensitive to repeated stress-related diarrhoea. The PICRUSt2 of metagenomic function analysis found that repeated stress-related diarrhoea is more likely to perturb the intestinal mucosa microbiota metagenomic functions involved in the neural response. We further found that the mucosal microbiota-based relative abundance model was more predictive on serum 5-HT concentration with the methods of machine learning model established and multivariate dimensionality reduction (R2 = 0.876). These findings suggest that the intestinal mucosa microbiota might serve as a novel potential prediction model for the serum 5-HT concentration involvement in the repeated stress-related diarrhoea, in addition to focusing on its mechanism in the gastrointestinal dysfunction.